An investigation into the parameters governing the interrelationship between temporal fenestrae and associated jaw adductor muscles in selected lacertilians - Welman, J.(Johann) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1982.